Developmental regulation of ecdysone receptor (EcR) and EcR-controlled gene expression during pharate-adult development of honeybees (Apis mellifera) - Mello, Tathyana R. P.; Aleixo, Aline C.; Pinheiro, Daniel G.; Nunes, Francis M. F.; Bitondi, Márcia M. G.; Hartfelder, Klaus; Barchuk, Angel R.; Simões, Zilá L. P. (Frontiers in Genetics, 2014)
Major developmental transitions in multicellular organisms are driven by steroid hormones. In insects, these, together with juvenile hormone (JH), control development, metamorphosis, reproduction and aging, and are also suggested to play an important role in caste differentiation of social insects. Here, we aimed to determine how EcR transcription and ecdysteroid titers are related during honeybee postembryonic development and what may actually be the role of EcR in caste development of this social insect. In addition, we expected that knocking-down EcR gene expression would give us information on the participation of the respective protein in regulating downstream targets of EcR. We found that in Apis mellifera females, EcR-A is the predominantly expressed variant in postembryonic development, while EcR-B transcript levels are higher in embryos, indicating an early developmental switch in EcR function. During larval and pupal stages, EcR-B expression levels are very low, while EcR-A transcripts are more variable and abundant in workers compared to queens. Strikingly, these transcript levels are opposite to the ecdysteroid titer profile. 20-hydroxyecdysone (20E) application experiments revealed that low 20E levels induce EcR expression during development, whereas high ecdysteroid titers seem to be repressive. By means of RNAi-mediated knockdown (KD) of both EcR transcript variants we detected the differential expression of 234 poly-A+ transcripts encoding genes such as CYPs, MRJPs and certain hormone response genes (Kr-h1 and ftz-f1). EcR-KD also promoted the differential expression of 70 miRNAs, including highly conserved ones (e.g. miR-133 and miR-375), as well honeybee-specific ones (e.g. miR-3745 and miR-3761). Our results put in evidence a broad spectrum of EcR-controlled gene expression during postembryonic development of honeybees, revealing new facets of EcR biology in this social insect.